Application of thermosetting plastic in preparation of hydrophobic concrete and product

By adding thermosetting plastic powder and polyacrylamide to cement concrete, combined with quartz sand and fly ash, the problem of cement concrete being easily infiltrated in the water environment is solved, and the deep hydrophobic effect and mechanical properties are improved, avoiding the Resource waste and environmental pollution have broad application prospects.

CN119263669APending Publication Date: 2025-01-07WENZHOU MOTAI MORTAR TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411281148.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The problem of existing cement concrete being prone to infiltrating in water environments leads to waste of resources and environmental pollution, and the existing hydrophobic improvement technology relies on a variety of organic compounds to affect performance and the environment.

Method used

By adding thermosetting plastic powder to concrete, combining cement, quartz sand and polyacrylamide, the hydrophobicity and mechanical properties are improved, and polyacrylamide is used as a water reducer and dispersant to form a deep hydrophobic effect.

Benefits of technology

It has achieved low surface porosity, excellent hydrophobic effect, good impact resistance, improved freeze-thawing properties and no reduction in the mechanical strength of concrete. It has effectively utilized solid waste resources and has wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263669A_ABST
    Figure CN119263669A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and discloses application of thermosetting plastic in preparation of hydrophobic concrete and a product. The hydrophobic concrete product is prepared from the following ingredients in parts by mass: 10 to 60 parts of thermosetting plastic powder, 20 to 30 parts of cement, 5 to 50 parts of quartz sand, 5 to 10 parts of fly ash and 25 to 35 parts of polyacrylamide-containing aqueous solution. The concentration of the polyacrylamide is 0 to 8000 ppm. According to the concrete product provided by the invention, the hydrophobic property of the concrete product is improved, the water absorption rate is reduced, the mechanical strength of cement is not greatly reduced, solid waste resources are effectively utilized, and the concrete product has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, relates to improvement of the hydrophobicity of concrete, and in particular to application of thermosetting plastics in the preparation of hydrophobic concrete and products. Background Art

[0002] Cement concrete systems often need to be exposed to water environments such as rivers, oceans, and high humidity. Due to the porosity and hydrophilicity of cement concrete, a large amount of water will infiltrate into the pores of cement-based materials. The relevant industry has done a lot of product development and research on the waterproof performance of cement concrete. In order to achieve the hydrophobic performance of cement concrete, products such as wax, organic ketones, and silane coupling agents are used to improve the surface hydrophobicity of cement products. Patent application CN202410362701.3 discloses a hydrophobic concrete, including a cementitious material and an admixture. The cementitious material includes a hydraulic and modified fly ash in a mass ratio of (1-3): 1; the admixture includes a hydrophobic agent, a water reducer, and calcium stearate; the modified fly ash is obtained by mixing fly ash and an alcohol substance in a mass ratio of (3-7): 1; the hydrophobic agent includes an organic siloxane; and the water reducer is a polycarboxylate-based water reducer.

[0003] It can be seen that the preparation of existing hydrophobic concrete requires the use of a lot of additional organic compounds, which not only causes a waste of resources, but also has a negative impact on the environment and cement concrete. Summary of the invention

[0004] In view of the problems of resource waste and environmental pollution in the prior art of improving the hydrophobicity of cement concrete, the present invention aims to provide an application of thermosetting plastics in the preparation of hydrophobic concrete, thereby improving the hydrophobicity of concrete by adding thermosetting plastics.

[0005] Another object of the present invention is to provide a hydrophobic concrete product and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions to achieve it.

[0007] The invention provides application of thermosetting plastic in preparing hydrophobic concrete.

[0008] The thermosetting plastic is a thermosetting plastic powder, which is obtained by crushing a solid waste thermosetting plastic product; the mesh number of the powder after crushing is greater than 600 mesh; in a preferred implementation, the mesh number of the powder after crushing is greater than 1000 mesh. The solid waste thermosetting plastic product can be crushed by the thermosetting resin processing device disclosed in patent application CN202320568950.9.

[0009] The solid waste thermosetting plastic product can be derived from industrial solid waste thermosetting plastic products or domestic thermosetting plastic products, such as electrical components, wind turbine blades, auto parts, etc. The main component of thermosetting plastic products is thermosetting resin, and thermosetting plastic powder itself has hydrophobicity. When thermosetting plastic powder is added to concrete preparation, after the powderization process, the surface oxygen-containing chemical groups increase, which increases the bonding ability during the cement curing process, reduces the negative impact of the side wall effect, and improves the mechanical properties of cement products.

[0010] Furthermore, the thermosetting plastic product mainly contains epoxy resin and / or does not contain polyester resin, and may also contain inevitable impurities.

[0011] The present invention also provides a hydrophobic concrete product, which comprises, by weight, 10-60 parts of thermosetting plastic powder, 20-30 parts of cement, 5-50 parts of quartz sand, 5-10 parts of fly ash, and 25-35 parts of an aqueous solution containing polyacrylamide; the concentration of the polyacrylamide is 0-8000ppm.

[0012] In addition to the aforementioned role of thermosetting plastic powder, the above-mentioned hydrophobic concrete product uses polyacrylamide as a water reducer and dispersant to improve the processability, plasticity and curing speed of concrete materials. Constructing cement aggregates with fly ash and quartz sand can improve the compressive strength and structural strength of cement products.

[0013] In a preferred implementation, the above-mentioned hydrophobic concrete product comprises, by weight, 20-30 parts of thermosetting plastic powder, 20-30 parts of cement, 5-50 parts of quartz sand, 5-10 parts of fly ash, and 25-35 parts of an aqueous solution containing polyacrylamide; the concentration of the polyacrylamide is 2000-4000ppm.

[0014] The above-mentioned hydrophobic concrete product, the thermosetting plastic powder is as described above.

[0015] In the above hydrophobic concrete product, the cement is silicate cement; the mesh number of the quartz sand is 100-120 meshes; and the particle size of the fly ash is 50-200 μm.

[0016] In the above hydrophobic concrete product, the molecular weight of the polyacrylamide is 50,000-5 million, preferably 100,000-1 million. The polyacrylamide aqueous solution is used to reduce the internal friction of the concrete, effectively disperse thermosetting plastic powder, cement, fly ash, quartz sand and other aggregates, and improve the plasticity and curing speed of the concrete through gel network cross-linking.

[0017] The present invention also provides a method for preparing the hydrophobic concrete product, which is obtained by uniformly mixing thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide according to the above-mentioned proportions of ingredients.

[0018] The above concrete product is poured into a set mold and further cured to obtain a final concrete product, such as a pipe, a wall section, a roadbed, a plate, and other concrete products. Here, a conventional curing method for preparing cement concrete can be used.

[0019] In summary, compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The concrete product provided by the present invention has low surface porosity and excellent surface hydrophobic effect, and the material components inside and outside the concrete are uniform and have a deep hydrophobic effect;

[0021] (2) The concrete product provided by the present invention has a soft and hard phase based on the added thermosetting plastic, and has good impact resistance and energy absorption effect (i.e., recoverable elasticity);

[0022] (3) The concrete product provided by the present invention has excellent hydrophobic properties and low water absorption, thereby improving the freeze-thaw properties of concrete;

[0023] (4) The concrete product provided by the present invention improves the hydrophobicity of the concrete product without significantly reducing the mechanical strength of cement, thereby not affecting the application of concrete;

[0024] (5) The present invention uses thermosetting plastic as an additive and effectively makes concrete or mortar hydrophobic by mixing raw materials such as cement, fly ash, quartz sand, polyacrylamide, etc. without significantly damaging the performance of the concrete. It can also effectively utilize solid waste resources and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Images collected for contact angle testing of finished concrete samples prepared in Examples and Comparative Examples; wherein (a) corresponds to Comparative Example 1, (b) corresponds to Example 1, (c) corresponds to Example 8, and (d) corresponds to Example 3;

[0026] Figure 2 Images collected for porosity testing of finished concrete samples prepared in Examples and Comparative Examples; wherein (a) corresponds to Comparative Example 1, (b) corresponds to Example 1, (c) corresponds to Example 8, and (d) corresponds to Example 3. DETAILED DESCRIPTION

[0027] The following will clearly and completely describe the technical solutions of various embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] The cement used in the following examples and comparative examples is Portland cement 525.

[0029] The mesh number of the quartz sand used in the following examples and comparative examples is 100-120 meshes.

[0030] The fly ash particle size used in the following examples and comparative examples is 50-200 μm.

[0031] The molecular weight of the polyacrylamide used in the following examples and comparative examples is 1 million.

[0032] The thermosetting plastic powder used in the following embodiments is obtained by crushing industrial solid waste thermosetting plastic products electrical components, wind blades, and auto parts to a size of 1000 mesh or more using the thermosetting resin processing device disclosed in CN202320568950.9. The components of the electrical components, wind blades, and auto parts mainly include epoxy resin and do not include polyester resin, and may also include unavoidable impurities.

[0033] In the following examples, concrete curing was carried out in accordance with the relevant provisions of GB / T17671, and the curing period was 28 days.

[0034] Example 1

[0035] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by mass, 10 parts of thermosetting plastic powder, 30 parts of cement, 50 parts of quartz sand, 10 parts of fly ash, and 30 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 8000 ppm.

[0036] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0037] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0038] Example 2

[0039] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by mass, 20 parts of thermosetting plastic powder, 30 parts of cement, 45 parts of quartz sand, 5 parts of fly ash, and 30 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 8000 ppm.

[0040] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0041] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0042] Example 3

[0043] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by mass, 30 parts of thermosetting plastic powder, 30 parts of cement, 35 parts of quartz sand, 5 parts of fly ash, and 30 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 8000 ppm.

[0044] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0045] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0046] Example 4

[0047] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by mass, 60 parts of thermosetting plastic powder, 30 parts of cement, 5 parts of quartz sand, 5 parts of fly ash, and 30 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 8000 ppm.

[0048] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0049] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0050] Example 5

[0051] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by mass, 20 parts of thermosetting plastic powder, 30 parts of cement, 45 parts of quartz sand, 5 parts of fly ash, and 30 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 4000 ppm.

[0052] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0053] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0054] Example 6

[0055] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by weight: 20 parts of thermosetting plastic powder, 30 parts of cement, 45 parts of quartz sand, 5 parts of fly ash, and 30 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 1000 ppm.

[0056] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0057] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0058] Example 7

[0059] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by weight, 20 parts of thermosetting plastic powder, 30 parts of cement, 45 parts of quartz sand, 5 parts of fly ash, and 30 parts of water.

[0060] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash and water are uniformly mixed according to the above-mentioned proportions of ingredients.

[0061] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0062] Example 8

[0063] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by weight: 20 parts of thermosetting plastic powder, 20 parts of cement, 50 parts of quartz sand, 10 parts of fly ash, and 30 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 8000 ppm.

[0064] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0065] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0066] Example 9

[0067] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by weight: 20 parts of thermosetting plastic powder, 20 parts of cement, 50 parts of quartz sand, 10 parts of fly ash, and 25 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 6000 ppm.

[0068] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0069] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0070] Example 10

[0071] The ingredients for preparing the hydrophobic concrete product provided in this embodiment include, by weight: 20 parts of thermosetting plastic powder, 20 parts of cement, 50 parts of quartz sand, 10 parts of fly ash, and 35 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 4000 ppm.

[0072] The preparation method of the concrete product provided in this embodiment is as follows: thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-mentioned proportions of ingredients.

[0073] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0074] Comparative Example 1

[0075] The ingredients of the concrete product provided in this comparative example include: 30 parts of cement, 60 parts of quartz sand, 10 parts of fly ash, and 30 parts of an aqueous solution containing polyacrylamide, wherein the concentration of the polyacrylamide is 8000 ppm.

[0076] The preparation method of the concrete product provided in this comparative example is: cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide are uniformly mixed according to the above-given ingredient ratios to obtain the concrete product.

[0077] The concrete product was poured into a mold and further cured for 28 days to obtain the final concrete product sample.

[0078] The finished concrete samples of Examples 1-8 and Comparative Example 1 were subjected to contact angle test, compression test, three-point bending test, freeze-thaw test times, and water absorption test. The test results are shown in Table 1.

[0079] Contact angle (°) Compression test (MPa) Three-point bending (MPa) Freeze-thaw test times (times) <![CDATA[Water absorption rate (g / cm 3 )]]> Comparative Example 1 14.2 54.6 1.18 8 0.39 Example 1 78.5 49.3 0.96 12 0.36 Example 2 120.5 46.7 0.85 27 0.18 Example 3 134.6 42.2 0.80 33 0.13 Example 4 143.7 28.8 0.52 36 0.08 Example 5 119.4 48.5 0.87 23 0.16 Example 6 117.1 48.6 0.86 22 0.19 Example 7 114.8 47.5 0.84 21 0.21 Example 8 122.2 34.1 0.71 18 0.18

[0080] For the test method of freeze-thaw test times, please refer to the national standard GB / T 41060-2021.

[0081] The contact angle test results of the finished concrete samples prepared in Comparative Example 1, Example 1, Example 8 and Example 3 are as follows: Figure 1 As shown in Table 1, it can be seen that the finished concrete sample prepared by the method of the present invention has excellent hydrophobic properties, especially with the increase of thermosetting plastic powder, the hydrophobic properties are more excellent. And by adjusting the proportion of cement, quartz sand and fly ash, the contact angle can be adjusted.

[0082] The porosity test results of the finished concrete samples prepared in Comparative Example 1, Example 1, Example 8 and Example 3 are as follows: Figure 2 As shown in the figure, it can be seen that the porosity of the finished concrete sample prepared by the method of the present invention is very small, and as the thermosetting plastic powder increases, the porosity gradually decreases. This can also be seen from the water absorption test results in Table 1 that the water absorption of the finished concrete sample prepared by the method of the present invention is low, and the surface sample is dense, which is consistent with the porosity test results.

[0083] In addition, it can be seen from Table 1 that the finished concrete sample prepared by the method of the present invention can maintain good mechanical properties while improving the hydrophobicity of the material.

[0084] It can be seen from the number of freeze-thaw tests that the method of the present invention can effectively improve the freeze-thaw resistance of cement products, ensure that the performance of cement products in cold environments meets the requirements, and improve the durability and safety of buildings.

[0085] Those skilled in the art will appreciate that the embodiments herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.

Claims

1. Application of thermosetting plastics in the preparation of hydrophobic concrete.

2. The use according to claim 1, characterized in that: The thermosetting plastic is thermosetting plastic powder.

3. The use according to claim 2, characterized in that: The thermosetting plastic powder is obtained by crushing solid waste thermosetting plastic products; the powder mesh size after crushing is greater than 600 meshes.

4. The use according to claim 3, characterized in that: The solid waste thermosetting plastic product comes from industrial solid waste thermosetting plastic products or domestic thermosetting plastic products.

5. The use according to claim 4, characterized in that: The thermosetting plastic product mainly contains epoxy resin and / or does not contain polyester resin.

6. A hydrophobic concrete product, characterized in that: The ingredients include 10-60 parts of thermosetting plastic powder, 20-30 parts of cement, 5-50 parts of quartz sand, 5-10 parts of fly ash, and 25-35 parts of aqueous solution containing polyacrylamide by weight; the concentration of the polyacrylamide is 0-8000ppm.

7. The hydrophobic concrete product according to claim 6, characterized in that: The ingredients include 20-30 parts of thermosetting plastic powder, 20-30 parts of cement, 5-50 parts of quartz sand, 5-10 parts of fly ash, and 25-35 parts of aqueous solution containing polyacrylamide by weight; the concentration of the polyacrylamide is 2000-4000ppm.

8. The hydrophobic concrete product according to claim 6, characterized in that: The cement is silicate cement.

9. The hydrophobic concrete product according to claim 6, characterized in that: The mesh number of the quartz sand is 100-120 meshes; the particle size of the fly ash is 50-200 μm.

10. A method for preparing a hydrophobic concrete product, characterized in that: The hydrophobic concrete product according to any one of claims 6 to 9 is obtained by uniformly mixing thermosetting plastic powder, cement, quartz sand, fly ash, and an aqueous solution containing polyacrylamide.

Citation Information

Patent Citations

  • Hydrophobic concrete

    CN118290088A

  • Thermosetting resin treatment device

    CN219381214U